2002
DOI: 10.1530/eje.0.1470495
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Pro12Ala polymorphism of the peroxisome proliferator-activated receptor gamma-2 gene on adiposity, insulin sensitivity and lipid profile in the Spanish population

Abstract: Objective: To investigate the role of the Pro12Ala peroxisome proliferator-activated receptor (PPAR) g-2 polymorphism in the susceptibility to the insulin resistance syndrome and its metabolic complications in a population-based nationwide multicenter study in Spain. Design: 464 unrelated adults (45.3% men and 54.7% women) aged between 35 and 64 years were randomly chosen from a nationwide population-based survey of obesity and related conditions including insulin resistance and cardiovascular risk factors. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
43
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(52 citation statements)
references
References 43 publications
9
43
0
Order By: Relevance
“…In our sample of BSS cases, we found the Pro12Ala polymorphism in 13.7% and the Ala12 allele in 6.85%, findings that are compatible with Caucasian samples in different countries, as follows: 12.6% in Danes [23], 15.38% in American Caucasians [18], 12% in Italians [24] and 16.1% in Spaniards [20]. However, our results were slightly lower than those obtained for Finns (27.33%) [19] and Swedes (32.39%) [25].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In our sample of BSS cases, we found the Pro12Ala polymorphism in 13.7% and the Ala12 allele in 6.85%, findings that are compatible with Caucasian samples in different countries, as follows: 12.6% in Danes [23], 15.38% in American Caucasians [18], 12% in Italians [24] and 16.1% in Spaniards [20]. However, our results were slightly lower than those obtained for Finns (27.33%) [19] and Swedes (32.39%) [25].…”
Section: Discussionsupporting
confidence: 83%
“…Similarly, Spanish women with the Ala12 allele are more sensitive to insulin and have better lipid profiles than those with the Pro12Pro genotype and a lower prevalence of DM2. These findings suggest that the Pro12Ala polymorphism promotes decreased peripheral deposition of adipose tissue and increased insulin sensitivity [20]. …”
Section: Discussionmentioning
confidence: 99%
“…Nine cohort studies [12,25,26,27,28,29,30,31,32], 7 population case-control studies [33,34,35,36,37,38,39], 31 cross-sectional studies [5,7,10,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67], and 9 interventional studies [8,68,69,70,71,72,73,74,75] were included in the meta-analysis of the association between PPARγ Pro12Ala polymorphism and obesity. The characteristics and results of the studies are summarized in table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics and results of the studies are summarized in table 1. Seven population case-control studies [33,34,35,36,37,38,39], and 1 cross-sectional study [10] provided their data in 2 datasets. Each dataset was treated as a separate comparison in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the presence of other doi: 10.7243/2054-1112-2-1 vascular risk factors has also been explored in relation to the association between PPAR-γ and the onset of T2D. Similarly, other studies have demonstrated the PPAR-γ/T2D onset in association with Body Mass Index lipid profiles, also extending studies to secondary organ damage resulting from diabetes, diabetic nephropathy and coronary heart disease [19][20][21][22].…”
Section: Context and Previous Literaturementioning
confidence: 99%